2011
DOI: 10.1186/1752-1947-5-269
|View full text |Cite
|
Sign up to set email alerts
|

Precursor B-cell acute lymphoblastic leukemia presenting as obstructive jaundice: a case report

Abstract: IntroductionAcute leukemias very rarely present with jaundice. Herein we report a case of precursor B-cell acute lymphoblastic leukemia that presented with jaundice in an adult.Case presentationA 44-year-old Hispanic man presented with right upper quadrant abdominal pain and jaundice. His initial blood work revealed pancytopenia and hyperbilirubinemia. Direct bilirubin was more than 50% of the total. His imaging studies were unremarkable except for hepatomegaly. All blood screening tests for various hepatocell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…While there are reports in the literature of pediatric B-cell ALL and adult T-ALL presenting with cholestasis, we found none describing cholestatic jaundice as the presenting symptom in pediatric T-ALL. 1113…”
Section: Discussionmentioning
confidence: 99%
“…While there are reports in the literature of pediatric B-cell ALL and adult T-ALL presenting with cholestasis, we found none describing cholestatic jaundice as the presenting symptom in pediatric T-ALL. 1113…”
Section: Discussionmentioning
confidence: 99%
“…These receptors bind to the chemokine stromal-cell-derived factor-1 (SDF-1), a potent molecule for chemotaxis of lymphocytes found in the bone marrow and other tissues [14]. Rare cases of pancreatic and hepatic involvement with extrahepatic and intrahepatic bile duct obstruction causing cholestatic jaundice as an initial presentation have also been reported in adult ALL [6, 7].…”
Section: Discussionmentioning
confidence: 99%
“…Daniel et al reported the first case of obstructive jaundice from pancreatic masses compressing the common bile duct (CBD) in adult ALL [7]. Another rare case of leukemic infiltration of hepatic sinusoids resulting in cholestasis without pancreatic involvement was described by Siddique et al [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous case reports of lymphocytic leukemia have presented with cholestasis symptoms, but both were intrahepatic and diagnosed by liver biopsy. 6 , 7 A study of 6610 patients in MD Anderson Cancer Center to define the role of ERCP after hematopoietic stem cell transplant in patients presenting with jaundice, found that out of 40 patients that underwent ERCP, 17 had biliary strictures. From those 17, 76% (n = 13) were malignant.…”
Section: Discussionmentioning
confidence: 99%